Students’ Paraphrasing in the Literature Review Section of Research Proposal - Muhammad Taufiq Akbar (Jambura Journal of English Teaching and Literature, 2020)
The objective of this qualitative study is to investigate the students’ paraphrasing in the literature review section of research proposal. Six English Department students, Universitas Negeri Gorontalo were selected as the respondents. The study reveals that the paraphrasing of three students falls under a moderate revision category, and the other three are in the category of near copy. Such a result is based on the results of the students’ paraphrasing and their understanding of the concepts of effective paraphrasing, namely comprehension of good paraphrasing, analytic reading skills and its correlation in applying paraphrasing strategies, and citation mechanics. On that ground, the study suggests that improving students’ concept of paraphrasing in reviewing the literature is a necessity. Related stakeholders are urged to help the students understand the idea of quality paraphrasing. Further research about paraphrasing to investigate other relevant issues and other textual borrowing mechanics is essential.